Concentrations of metals and POPs in liver tissue of wild sea bird chicks from the Norwegian arctic region - Marit Nøst Hegseth; Francesco Regoli; Stefania Gorbi; Raffaella Bocchetti; Geir W Gabrielsen; Lionel Camus (PANGAEA, 2011)
Lysosomal membrane stability, lipofuscin (LF), malondialdehyde (MDA), neutral lipid (NL) levels, as well as halogenated organic compounds (HOCs), Cr, Cd, Pb and Fe concentrations were analyzed in liver of black-legged kittiwake (BK), herring gull (HG), and northern fulmar (NF) chicks. There were significant species differences in the levels of NL, LF and lysosomal membrane stability. These parameters were not associated with the respective HOC concentrations. LF accumulation was associated with increasing Cr, Cd and Pb concentrations. HG presented the lowest lysosomal membrane stability and the highest. LF and NL levels, which indicated impaired lysosomes in HG compared to NF and BK. Lipid peroxidation was associated with HOC and Fe2+ levels. Specific HOCs showed positive and significant correlations with MDA levels in HG. The study indicates that contaminant exposure can affect lysosomal and lipid associated parameters in seabird chicks even at low exposure levels. These parameters may be suitable markers of contaminant induced stress in arctic seabirds.
Supplement to: Hegseth, MN et al. (2011): Lysosomal and lipid-associated parameters in the livers of three species of arctic seabird chicks: Species differences and relationships with contaminant levels. Marine Pollution Bulletin, 62(8), 1652-1660, https://doi.org/10.1016/j.marpolbul.2011.06.011